The boy who could fly - Norcliffe, James, 1946- (Egmont USA, 2010)
Having grown up in a miserable home for abandoned children, a young boy jumps at the chance to exchange places with the mysterious, flying "loblolly boy," but once he takes on this new identity, he discovers what a harsh price he must pay.